PENERAPAN MODUL AJAR BERKARAKTERISTIK NON SMART DI SDN 6 LANGKAI - Meysa Mardalena Sari; Helnita Helnita; David Daniel Alex (JIP: Jurnal Ilmu Pendidikan, 2024)
This study aims to describe the implementation of non-smart characteristic teaching modules at SDN 6 Langkai and analyze their impact on the quality of learning. The non-smart teaching module referred to here is a teaching module that does not intensively utilize digital technology, but rather focuses more on conventional teaching methods such as lectures, discussions, and direct practice. This research uses a qualitative descriptive method with a case study approach. Data were collected through observations, interviews with teachers and students, as well as documentation of teaching modules and lesson plans. The research results depict the process of implementing the teaching module, the challenges faced, and the responses of teachers and students to the implementation of the teaching method.